Improved therapeutic efficacy of quercetin-loaded polymeric nanoparticles on triple-negative breast cancer by inhibiting uPA. Issue 57 (17th September 2020) - Zhou, Yang; Chen, Dan; Xue, Guangpu; Yu, Shujuan; Yuan, Cai; Huang, Mingdong; Jiang, Longguang
Abstract : Triple negative breast cancer (TNBC) is one kind of breast cancer that demonstrates highly aggressive tumor biology. Abstract : Triple negative breast cancer (TNBC) is one kind of breast cancer that demonstrates highly aggressive tumor biology. The high heterogeneity of TNBC makes its individual clinical treatment extremely blind and limited, which also introduces more challenges into the diagnosis and treatment of diseases. Urokinase-type plasminogen activator (uPA) is a high level marker for breast cancer, which mediates tumor growth and metastasis. Quercetin is a plant-derived flavonoid in many plants, which inhibits uPA and has low bioavailability and mediocre pharmaceutical efficacy. Thus, we herein developed polymeric nanoparticulate systems from PLGA-TPGS (Qu-NPs) for quercetin oral delivery and evaluated the anticancer effect of this formulation on TNBC in vitro and in vivo . Qu-NPs have a uniform spherical morphology with a mean diameter of 198.4 ± 7.8 nm and good drug loading capacity (8.1 ± 0.4%). Moreover, Qu-NPs exhibited significantly improved inhibition on the growth and metastasis in TNBC cells. Following oral gavage, a remarkable antitumor effect of Qu-NPs on 4T1-bearing mice was observed with a tumor inhibition ratio of 67.88% and fewer lung metastatic colonies. Furthermore, the inhibitory effect of quercetin on the migration of uPA knockdown MDA-MB231 cells was greatly attenuated. Together, Qu-NPs improved the significant antitumor and antimetastatic effects by inhibiting uPA, which provides a new strategy for the treatment of TNBC.